Therapeutic alliance, group climate, and client self-efficacy: influences on outcome in group therapy for driving anger reduction - Schwartz, Ethan, author; Deffenbacher, Jerry L., advisor; Hamilton, Scott B., committee member; Boyer, William N., committee member; Sample, Pat L., committee member (Colorado State University. Libraries, 2004)
This study examined how working alliance, group climate, and client self-efficacy related to each other and to outcome in group treatment of driving anger. Self-report measures of driving and general anger and driving and general anger expression were collected from 74 introductory psychology students who scored in the upper quartile on a measure of driving anger, indicated a personal problem with driving anger, and indicated a desire for counseling for driving anger reduction. Outcome was assessed on a pretreatment, post-treatment, and one-month follow-up basis. Clients participated in eight weeks of group therapy that utilized cognitive, behavioral, or relaxation interventions. The Working Alliance Inventory-Short Form, the Group Climate Questionnaire-Short Form, and a measure of self-efficacy regarding the use of anger reduction techniques when driving were gathered after the third and seventh sessions. Working alliance, self-efficacy, group engagement, and group conflict were reliable measures, but group avoidance was not. Working alliance and group cohesion were positively associated with positive outcomes, but relationships were generally small and inconsistent across measures. Group engagement, a measure of group cohesion, was the best predictor of outcomes of the group climate measures and was a better predictor than working alliance. Self-efficacy also correlated with positive outcomes, but relationships were small to moderate in size. Self-efficacy was the best predictor of reduction in driving anger. Although the set of predictors taken together accounted for a substantial portion of the variance in driving anger reduction, no single combination of factors proved to be the best predictors across measures. In terms of prediction of outcome, third session assessment of therapy variables appeared to be no better than seventh session assessment of therapy variables. Findings offer some evidence that working alliance, group climate, and self-efficacy are related to outcomes in a time-limited group treatment of driving anger. These variables predicted driving anger reduction, but did not fully explain variance in outcomes. Implications for future research and treatment were explored.
Keywords: psychotherapy; clinical psychology